Eruptive naevi associated with encorafenib for metastatic colorectal cancer: two cases. (1st October 2022) - Alfallouji, Yasmin; Spencer, Ashley; Calonje, Eduardo; Perrett, Conal M.; Watchorn, Richard; Borysiewicz, Catherine; Hodgkinson, Tara; Wasan, Harpreet; Bunker, Christopher B.; Sidwell, Rachel U.
Abstract: Encorafenib is a BRAF inhibitor increasingly used as a second‐line treatment for metastatic melanoma and colorectal cancer. BRAF inhibitors have been reported to be associated with new and changing melanocytic lesions, including eruptive naevi. We describe two cases of eruptive naevi secondary to encorafenib used for the treatment of BRAF‐mutant metastatic colorectal cancer.